Hierarchical composite fabrication by constructing Ni-encapsulated carbon nanotubes on N-doped carbon nanonets for high-performance absorbers - Hao, Zhilei; Shi, Shaoqi; Wang, Baojun; Liu, Pei; Gao, Qingqing; Xu, Kai; Ni, Yinxu; Tian, Zhaoxia; Xiao, Wei; Xu, Gaojie; Zhang, Hui; Liu, Fenghua (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
[Display omitted] •Using 3D N-doped carbon hollow nanonetworks (NCNs) derived from the annealing of polypyrrole (PPy) as a conductive substrate, the 3D NCNs offering interconnected pathways for charge carriers and enhancing conductive loss.•By employing high-temperature annealing to catalyze Ni nanoparticles as catalysts to induce the in-situ growth of 1D carbon nanotubes (CNTs) on the 3D conductive NCNs substrate, achieving the encapsulation of 0D magnetic Ni nanoparticles at the ends of the CNTs.•The synergy of highly dispersed Ni nanoparticles forming a magnetic coupling network and numerous heterogeneous interfaces with carbon nanotubes, greatly optimizes magnetic loss and polarization loss capability. Carbon-based materials are pivotal research subjects in the electromagnetic microwave absorption (EMA) field because they are lightweight, low cost, and possess high electrical conductivity. However, many limitations still exist for practical applications, such as limited absorption bandwidth, weak absorption performance, and impedance mismatch. In this study, N-doped carbon nanonets (NCNs) that are derived from polypyrrole (PPy) are used as the conductive matrix. Ni nanoparticles serve as catalysts to induce the in situ growth of 1D carbon nanotubes (CNTs) on a 3D conductive NCNs substrate through high-temperature annealing. This achieves the encapsulation of 0D magnetic Ni nanoparticles at the ends of the CNTs, resulting in the successful fabrication of Ni/CNTs/NCNs hierarchical nanostructured composites. The derived 1D CNTs with the 3D NCNs not only expand the conductive network and enhance conduction losses, but they also contribute to impedance matching and facilitate the dissipation of the electromagnetic waves (EMW). The 3D magnetic coupling network constructed by the Ni nanoparticles facilitates the formation of plenteous heterogeneous interfaces with CNTs, and the magnetic loss capability and interface polarization effect are effectively enhanced. The optimal reflection loss of the multilevel structured composites was −63.2 dB, and the effective absorption bandwidth covered 6.03 GHz.